1999
DOI: 10.1038/sj.ejhg.5200348
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of the fragile X knockout mouse brain studied using in vivo high resolution magnetic resonance imaging

Abstract: Magnetic resonance imaging (MRI) of the brain of fragile X patients, the most frequent form of inherited mental retardation, has revealed abnormalities in the size of specific brain structures, including the cerebellar vermis, the hippocampus, and the ventricular system. We intended to quantify the differences observed in the patient studies in the fragile X knockout mouse model, which is a good model for the disease, paralleling the human disorder in having cognitive deficits, macro-orchidism, and immature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Shortly, after the generation of the Fmr1 KO mouse in 1994 [80], the first MRI neuroanatomical assessment of the Fmr1 was performed [115]. Kooy et al [115] looked at the brains of 22 anesthetized mice in vivo (11 Fmr1 KO and 11 WT).…”
Section: Initial Investigations With Mri (1994-2010)mentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly, after the generation of the Fmr1 KO mouse in 1994 [80], the first MRI neuroanatomical assessment of the Fmr1 was performed [115]. Kooy et al [115] looked at the brains of 22 anesthetized mice in vivo (11 Fmr1 KO and 11 WT).…”
Section: Initial Investigations With Mri (1994-2010)mentioning
confidence: 99%
“…Shortly, after the generation of the Fmr1 KO mouse in 1994 [80], the first MRI neuroanatomical assessment of the Fmr1 was performed [115]. Kooy et al [115] looked at the brains of 22 anesthetized mice in vivo (11 Fmr1 KO and 11 WT). Images were acquired with high spatial resolution along the long axis of the mouse brain to assess the surface area of several different structures, including the total brain, cerebellum (anterior and posterior), fourth ventricle, subcortical gray matter, and hippocampus.…”
Section: Initial Investigations With Mri (1994-2010)mentioning
confidence: 99%
“…31 Early studies in the fragile X mouse found no brain volume changes. 32 However, another study showed significant volume decrease of the arbour vita of the cerebellum and more specifically of the deep cerebellar nuclei. Trends were found in the striatum (decrease) and the cerebral cortex of the parieto-temporal lobe (increase).…”
Section: Discussionmentioning
confidence: 99%
“…However, no abnormalities were found in the brain structures of the knockout mice that were previously identified in humans. 17 …”
Section: Neuroanatomic Mouse Studiesmentioning
confidence: 99%
“…Longitudinal studies on one and the same animal have been performed, 7 and volumetric measurements of different parts of the brain are feasible. 11,17 In general, with the aid of a specific mouse brain atlas 18 the various brain regions are readily identified as the MRI images resemble the histological sections. However, on MRI the size and shape of the various components of the ventricular system differ markedly from histological views.…”
Section: Lessons From Initial Studiesmentioning
confidence: 99%